Lack of Agreement on Fragmentation Metrics Blurs Correspondence between Fragmentation Experiments and Predicted Effects - Jan Bogaert (Ecology and Society, 2003)
The direct correspondence between landscape fragmentation and its effects is still the subject of debate. Many widely accepted hypotheses are not supported by experiments. The issue of fragmentation measurement is addressed here. To predict the effects of fragmentation, it is essential to quantify the pattern of fragmentation. Despite the increased use of spatial analysis and available measures, experts have not yet reached an agreement on how to measure patterns of fragmented landscapes and, thus, unambiguous translation of experimental findings into conservation or management guidelines is hampered.